Cannabinoids: Do they alleviate pain in cancer patients? - Waśniowska, Magdalena; Bujak, Magdalena; Stołowski, Wenancjusz; Czyżnikiewicz, Adrianna; Stadler-Szajda, Justyna; Prystacka-Szar, Dominika; Neska, Dagmara; Siemko, Jakub; Grabowski, Filip; Rulewska, Natalia (Journal of Education, Health and Sport, 2025)
More than half of cancer patients experience chronic pain, especially those who have the disease in an advanced stage. Cancer is a complex illness that causes substantial morbidity and mortality. The mainstay of traditional pain care is opioids, which, although useful for some people, usually lead to insufficient pain relief and a host of negative side effects, such as opioid-refractory pain and reliance. A growing number of people are interested in alternative treatment choices, including cannabinoids made from the cannabis plant, as a result of these difficulties. This review centers on the endocannabinoid system (ECS), a sophisticated network of cell signals that is essential for controlling a number of physiological and pathological functions, including the feeling of pain. Major cannabinoids including Δ9-tetrahydrocannabinol (THC) and cannabidiol (CBD) are being investigated for their potential to lessen the negative effects of chemotherapy as well as their analgesic and anti-inflammatory qualities. The promising role of cannabis in cancer pain management is highlighted in this review, which also discusses the need for more study to determine their safety, effectiveness, and incorporation into clinical practice. Methods A review of the literature was conducted using the WHO and PubMed databases. Keywords: oncology, chronic pain, pain, endocannabinoid system and cannaboids. A total of 33 papers or websites were included in the review.